2015
DOI: 10.4028/www.scientific.net/amr.1101.348
|View full text |Cite
|
Sign up to set email alerts
|

Potentiodynamic Polarization Studies of Glycerin in Platinum Electrodes

Abstract: <span><p class="TTPAbstract"><span lang="EN-US">A three electrode system was used for the analysis of potentiodynamic polarization studies of glycerin in platinum electrodes. Particular attention was devoted to the estimation of diffusion coefficient of glycerin in platinum electrodes by the use of electrochemical techniques such as the sweep of the potential. Cyclic voltammograms were recorded at different sweep rates (0.01 and 0.07 V·s-1). Randles-Sevcik equation was taken into consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Although Pt is the most active electrocatalyst for GOR in acidic media, it also suffers serious problems due to poisoning of Pt electrode . Meanwhile in alkaline medium, palladium and palladium based alloys have proven to be the most efficient and feasible substitutes to Pt . Moreover, it was found that the catalyst support played an effective role towards overall distribution of the metal nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Although Pt is the most active electrocatalyst for GOR in acidic media, it also suffers serious problems due to poisoning of Pt electrode . Meanwhile in alkaline medium, palladium and palladium based alloys have proven to be the most efficient and feasible substitutes to Pt . Moreover, it was found that the catalyst support played an effective role towards overall distribution of the metal nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical experiments were performed as described in [9]. Samples were taken at specific intervals of time and the analysis of the glycerol oxidation products was performed using a recent published method [10].…”
Section: Methodsmentioning
confidence: 99%